Research on the Path and Strategy of Traditional Chinese Medicine Talent Cultivation Based on Demand Orientation - Xu, Shuhong; Yu, Boyang (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Traditional Chinese Medicine (TCM) has shown unique advantages in the prevention and treatment of chronic complex diseases, emergency treatment and major infectious diseases, especially COVID-19 epidemic. Reformation and improvement of the talent cultivation mode with distinctive TCM characteristics is the approach to realize the high-quality development of TCM. Materials and Methods This paper systematically analyzed the development process of TCM talent cultivation in the past 15 years (2006–2020), comprehensively sorted out the current situation and main problems of TCM talent cultivation from the perspectives of discipline characteristics, industry needs and cultivation methods, and putted forward suggestions on the path of TCM talent cultivation in combination with the demands of serving a healthy China strategy and responding to the prevention and control of sudden epidemics. Results The study advocates for a demand-driven approach to TCM talent cultivation. Recommendations include focusing on TCM thinking, integrating master-apprentice and academic training, aligning talent structure with industry needs, diversifying teaching staff expertise, increasing customized talent supply, and promoting TCM internationalization. Conclusion This research emphasizes the importance of adapting TCM talent cultivation to meet the changing demands of healthcare. By addressing the identified challenges and implementing the proposed strategies, TCM education can better prepare professionals to contribute to a healthier society and effectively respond to future health challenges.
Keywords: Traditional Chinese medicine; Talent cultivation; Postgraduate education; Cultivation path.